2000
DOI: 10.1073/pnas.160070497
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of usher-mediated protein secretion and ordered pilus assembly

Abstract: Type 1 pilus biogenesis was used as a paradigm to investigate ordered macromolecular assembly at the outer cell membrane. The ability of Gram-negative bacteria to secrete proteins across their outer membrane and to assemble adhesive macromolecular structures on their surface is a defining event in pathogenesis. We elucidated genetic, biochemical, and biophysical requirements for assembly of functional type 1 pili. We discovered that the minor pilus protein FimG plays a critical role in nucleating the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 38 publications
(80 reference statements)
2
85
0
1
Order By: Relevance
“…on May 11, 2018 by guest http://jb.asm.org/ type 1 pili demonstrated that chaperone-subunit complexes could be purified from the OM as a complex with the FimD usher (27,28). We coexpressed WT PapC or PapC⌬2-11 with the PapD chaperone and the tip fibril subunits PapK, -E, -F, and -G. OM fractions from these bacteria were isolated and solubilized with the nondenaturing detergent DDM, and PapC was purified by its His tag with nickel beads.…”
Section: Vol 186 2004 Function Of the Usher N Terminus In Pilus Biomentioning
confidence: 99%
“…on May 11, 2018 by guest http://jb.asm.org/ type 1 pili demonstrated that chaperone-subunit complexes could be purified from the OM as a complex with the FimD usher (27,28). We coexpressed WT PapC or PapC⌬2-11 with the PapD chaperone and the tip fibril subunits PapK, -E, -F, and -G. OM fractions from these bacteria were isolated and solubilized with the nondenaturing detergent DDM, and PapC was purified by its His tag with nickel beads.…”
Section: Vol 186 2004 Function Of the Usher N Terminus In Pilus Biomentioning
confidence: 99%
“…The ushers (80 to 90 kDa) are somewhat larger than secretins. PapC, as well as its counterpart in type I pili secretion, FimD, forms ring-like structures, as shown by electron microscopy (579,655). These rings are 15 nm across and contain central pores 2 to 3 nm in diameter.…”
Section: Secretins Ushers and Autotransporters Producing Oligomericmentioning
confidence: 93%
“…The helical shaft has a diameter of 7 nm and consists of 3.4 copies of the FimA major subunit per turn (42, 122). The short tip fibrillum is composed of the FimF and FimG minor fimbrial subunits and carries the FimH tip adhesin at its distal end (122,163,279,291).…”
Section: The ␥-Fimbriaementioning
confidence: 99%